The theoretical basis of the right to environmental information - Романко, С. М. (Theory and practice of jurisprudence, 2016)
Problem setting. According to the evolution of human rights are divided into: the right of the first, second law and the rights of third generation depending ox historical era of society. However, in modern legal literature emerged ideas for possible allocation of a separate group of fourth-generation rights - human rights, in particular these include environmental law. In this respect the position deserves attention N. Kobetskoyi, which emphasizes that it is necessary to distinguish between the concept of "rights of citizens in environmental relations" and "environmental rights". She believes that the concept is much narrower first. The rights of citizens in environmental relations cover all of the powers which are somehow related to the environment, natural resources. General environmental law - a qualitatively new group of human and civil rights, which is different from the law of nature primarily focus on meeting environmental, rather than physical, spiritual and aesthetic needs and interests Recent research and publications analysis. It should be noted that this problem is reflected in the writings of many scientists. In particular, M. Volyk, S. Golub, V. Krayeva, L. Nechyporuk, V. Ovdiyenko, T. Suhorebroyi, P. Tihiy, A. Tomina. Paper objective. It consists in the study: the definition of "environmental information", its signs and types and characteristics of environmental and legal relations in determining the right to environmental information; the essence of the concept of "right to environmental information", its content, sources, subjects of the implementation of this law and its implementation mechanism enshrined in the current legislation of Ukraine; determining the characteristics of access to environmental information as a public information about the environment, carrying out separation of environmental information from business data. Paper main body. As the information is distributed, is available for hundreds of millions of people, it is becoming increasingly high financial power that affects not only the technical issues but also on the economy as a whole, social, environmental sector, the nature of modern thought and thinking. This manifests the complexity and urgency of the regulation of social relations in the field of acquisition, storage and dissemination of information. According to Art. 19 of the Universal Declaration of Human Rights, "Everyone has the right to freedom of opinion and expression; this right includes freedom to hold freely trans-nan and to seek, receive and impart information and ideas through any means and regardless of frontiers ". Similar provisions are contained in the Constitution of Ukraine - "Everyone has the right to freedom of opinion and speech, freedom of expression and belief. Everyone has the right to freely collect, use and disseminate information orally, in writing or otherwise - of their choice. Conclusions of the research. Based on the content of the information types listed above, it is logical to conclude that such a list is much better suited for a broad meaning of the term "environmental information" rather than the term "information about the state of the environment", which in fact mentioned in paragraph 1 of 1 Article 25 of the Law of Ukraine "On environmental Protection". However, it appears that the use of the law of double term "information about the state of the environment" (environmental information) and created this tautology in defining the legislature were made deliberately, because the definition introduced in national legislation, which has used the term "environmental information "in connection with ratification of the Aarhus Convention, which uses the term" environmental information ". Thus it was ensured that the constitutional guarantee of openness and access the information to classify the prohibition applies to the full range of environmental information listed in Article 25 of the Law of Ukraine "On Environmental Protection" and Article 2 of the Aarhus Convention. It should also be noted that there are difficulties associated with the realization of the right to environmental information that indicate very poor effective mechanism for regulation of these relations.